Ética en el cuidado de enfermería en personas portadoras del Virus de Inmunodeficiencia Humana. - Lopez De La Cruz, Nathaly Mishell (2025)
In a global context of spreading infections, the Human Immunodeficiency Virus (HIV) represents a critical public health challenge. This study examines the ethical conduct in nursing care for HIV-positive people, highlighting the importance of care that respects confidentiality, dignity, and patient autonomy to enhance adherence to therapy and reduce the associated stigma. Through a descriptive literature review in specialized scientific databases, 49 recent articles were selected. Given the vast number of studies on the subject, one might think that the most recent research would be the only valid source. However, it was decided to include articles from the years 2015 to 2017 in this work because they provide a solid and well-founded theoretical basis on ethical principles applied to the care of people with HIV, which remain relevant despite the evolving context, using key terms such as "Ethics AND HIV" and "Confidentiality OR Criminalization." The findings underscore the need for ethical nursing practice to mitigate discrimination and enhance the well-being of people with HIV. It is concluded that ethical care promotes therapeutic compliance and contributes to reducing stigma, recommending the implementation of training programs in professional ethics that favor humanized and equitable care, thus optimizing the social integration and quality of life of these patients.